Strategic Leadership to Deal with the Separatism Movement in Papua - Anandari, Anatansyah Ayomi; Supriyadi, Asep Adang (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
The separatist movement in Papua has been a threat to the sovereignty and territorial integrity of the Republic of Indonesia for many years. Although various efforts have been made to deal with this problem, the separatist movement still exists and threatens the stability of the Papua region. Therefore, effective strategic leadership policies and strategies are needed to overcome separatist movements in Papua. The purpose of this study is to analyze the role of strategic leadership in overcoming separatist movements in Papua as a form of threat to the sovereignty and territorial integrity of the Republic of Indonesia. The research method used is library research by collecting data from primary and secondary sources, including journal articles, books, and official documents. The data was then analyzed qualitatively using a descriptive approach. The recommendations for effective strategic leadership in addressing separatist movements in Papua include; acknowledging historical factors, engaging stakeholders, adopting preventive strategies, protecting human rights, leveraging technology, enhancing transparency and accountability, and promoting economic development.